Evaluation of community pharmacists' knowledge and attitude about Hajj and Umrah-related health conditions in the western region, Saudi Arabia: A cross-sectional study. - Nasser M Alorfi; Ahmed M Ashour; Maan H Harbi; Fahad S Alshehri (PLoS ONE)
Background During the Hajj and Umrah seasons in Saudi Arabia, pilgrims tend to experience a higher frequency of various health conditions. Respiratory infections, gastrointestinal infections, and food poisoning are among the most prevalent ailments. To address these health concerns, community pharmacists (CPs) have developed standardized treatment protocols. Pharmacists' skills in medication dispensing, health consultations, and preventive care enhance pilgrims' well-being in challenging pilgrimage settings. Aims The objective of this study was to investigate the knowledge and attitude of CPs towards health conditions related to Hajj and Umrah in the Western Region of Saudi Arabia where the Hajj and Umrah are taking place. Methods Between March and April 2023, an online cross-sectional study using Google form was carried out among CPs who work in the western region of Saudi Arabia. The study made use of a self-administered questionnaire consisting of four sections that aimed to obtain information about the CPs' knowledge and attitudes towards health conditions related to Hajj and Umrah. Data analysis was conducted using the Statistical Package for the Social Sciences version 26 (SPSS). Result A total of 496 CPs completed and returned the questionnaire, by giving a response rate of 99.2% (n = 500). Among them, 55.1% were aware of the necessary vaccines for Hajj and Umrah. Approximately 46.6% of CPs provided health-related advice to pilgrims. The most common health conditions experienced by pilgrims were diarrhea (59.5%), followed by flu and cough (58%), gastrointestinal diseases (39.4%), food poisoning (33.6%), viral fever, and heat stroke (24.4%). Regarding attitudes towards vaccination, 55.3% of CPs agreed that vaccination is safe for pilgrims aged 65 years and above, and 65.7% agreed that vaccination can help reduce medical costs during Hajj and Umrah seasons. Additionally, 61.1% of CPs recommended updating immunization against vaccine-preventable diseases for all travelers to ensure a safe Hajj and Umrah. The overall mean knowledge of CPs regarding vaccination during Hajj and Umrah was 4.739(2.49) (median = 5; Range = 0-9). However, 56.7% of CPs demonstrated good knowledge, while 43.3% reported poor knowledge regarding vaccination during Hajj and Umrah. Conclusion The community pharmacists (CPs) in the Mecca region were found to have good knowledge, with more than half of them having positive attitudes about vaccination for Hajj and Umrah-related health conditions. It is crucial to enhance the knowledge and attitudes of CPs to provide better care and participate in reliable and supportive healthcare and counseling sessions for managing various health infections.